Safety and immunogenicity of a quadrivalent influenza vaccine in adults 65 y of age and older - David P. Greenberg; Corwin A. Robertson; H. Keipp Talbot; Michael D. Decker (Human Vaccines & Immunotherapeutics, 2017)
Frequent mismatches between the predominant circulating B strain lineage and the B strain lineage in trivalent influenza vaccines have resulted in missed opportunities to prevent influenza illness. Quadrivalent influenza vaccines containing B strains from each of the 2 lineages have been developed for improved prevention of influenza B infections. Here, we describe the results of a phase III, randomized, double-blind, active-controlled, multicenter trial examining the safety and immunogenicity of a split-virion inactivated quadrivalent influenza vaccine (IIV4) in 675 adults ≥ 65 y of age (NCT01218646). Participants were randomly assigned 1:1:1 to receive a single intramuscular injection with the investigational IIV4, or one of 2 split-virion trivalent inactivated influenza vaccines (IIV3s): a licensed IIV3 containing a B Victoria-lineage strain or an investigational IIV3 containing a B Yamagata-lineage strain. Post-vaccination (day 21) hemagglutinin inhibition titers to all strains induced by IIV4 were statistically non-inferior to those induced by the 2 IIV3s. In addition, for each B strain, rates of seroconversion in the IIV4 group were superior to those induced by the comparator IIV3 not containing that B strain. For all vaccines, the most common solicited reaction was injection-site pain, and most reactions were mild to moderate in intensity and transient. Overall safety profiles were similar between IIV4 and the IIV3s, and no vaccine-related serious adverse events were reported. These results confirm that in adults ≥ 65 y of age, IIV4 was well tolerated and immunogenic against the additional B lineage strain without compromising the immunogenicity of the other 3 vaccine strains.